2020
DOI: 10.1371/journal.pone.0230842
|View full text |Cite
|
Sign up to set email alerts
|

Phage cocktail containing Podoviridae and Myoviridae bacteriophages inhibits the growth of Pectobacterium spp. under in vitro and in vivo conditions

Abstract: Globally, there is a high economic burden caused by pre-and post-harvest losses in vegetables, fruits and ornamentals due to soft rot diseases. At present, the control methods for these diseases are limited, but there is some promise in developing biological control products for use in Integrated Pest Management. This study sought to formulate a phage cocktail which would be effective against soft rot Pectobacteriaceae species affecting potato (Solanum tuberosum L.), with potential methods of application in ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 46 publications
(92 reference statements)
0
29
0
1
Order By: Relevance
“…There has been, however, an extensive amount of research on biocontrol of the most widespread economically important SRP, especially Dickeya solani , P. carotovorum and P. atrosepticum [ 5 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. In fact, biocontrol of SRP using bacteriophages has progressed the most among other methods, with a stage where formulated commercial product is available, including Biolyse ® , which was demonstrated to be efficacious at preventing soft rot in packaged potatoes caused by Pectobacterium and Dickeya species [ 141 ].…”
Section: Management and The Control Of Pbrmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been, however, an extensive amount of research on biocontrol of the most widespread economically important SRP, especially Dickeya solani , P. carotovorum and P. atrosepticum [ 5 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. In fact, biocontrol of SRP using bacteriophages has progressed the most among other methods, with a stage where formulated commercial product is available, including Biolyse ® , which was demonstrated to be efficacious at preventing soft rot in packaged potatoes caused by Pectobacterium and Dickeya species [ 141 ].…”
Section: Management and The Control Of Pbrmentioning
confidence: 99%
“…Carstens et al [ 136 ] reported significant suppression of soft rot caused by P. atrosepticum using a phage cocktail containing six selected bacteriophages on potato tubers in simulated storage conditions. The phage efficacy to control Pbr in field trials has not been reported so far [ 19 ], however, recently the efficacy of single bacteriophages or phage cocktails to control P. carotovorum and P. atrosepticum was proven under field conditions [ 14 , 138 , 139 ].…”
Section: Management and The Control Of Pbrmentioning
confidence: 99%
“…Studies of in vitro phage-host interactions in liquid culture commonly use optical density to compare bacterial growth dynamics in response to different phage treatments [18][19][20][21][22][23]. Optical density measurements are quick and amenable to high-throughput comparison using 96-well incubating spectrophotometers, and hosts can even be fluorescently labeled to allow differentiation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, postharvest application of Pectobacterium phages is allowed in Europe [4]. Numerous attempts have been made to systematize the application of individual phages and phage cocktails to protect potatoes from soft rot [4][5][6][7][8][9][10][11]. However, most studies were limited to in vitro conditions and model strains of the pathogens.…”
Section: Introductionmentioning
confidence: 99%